Serbian Society: Without a Past, What are we Today? - Manić, Mihajlo P. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
A review of Petar Anđelković's book: Serbian Society: Without a Past, What are we Today? (Kosovska Mitrovica: Faculty of Philosophy, 2013)